Quand l’écran masque l’expérience des opérateurs vieillissants : changement de logiciel et activité de travail dans un organisme de services - Corinne Gaudart (Perspectives Interdisciplinaires sur le Travail et la Santé)
How do elderly workers manage with technological changes ? This article presents the results of an ergonomic study, which tries to by-pass the usual stereotypes about age and work relationships. It analyses the process of introduction of a new software, in a French firm from the service industries where many middle-aged white collars are being employed. Which type of work strategies, linked to their professional experience, had these employees implemented with the former software ? How do the training methods, and the design of the software itself, allow or forbid to transfer old strategies towards the new situation The employees had formerly developed individual and collective operating modes, in order to anticipate and facilitate the relations with clients. These ways of doing were possible because of the flexibility of the software. The new one, more rigid and procedural, implies a more individualized activity, with a tight ranking of operations. Besides, when the employees came back to their workstations after training, important technical problems arose. This did not help them to consolidate their fresh theoretical knowledge. Therefore they settled in short run strategies aimed only at solving day-to-day difficulties. Everyone suffered from this situation, but especially the elderly : the possibility for them to transfer their ways of doing from one system to the other was all the more important that it allowed them to face time constraints. Nevertheless, employees, including the elderly, showed remarkable capacities to adapt themselves. A few months after this painful period, they started appropriating new spaces of dialogue which, should these strategies become more widespread, will allow them to rebuild partly their former operating modes. The study shows that difficulties among elderly workers are due to technical options in designing which do not take into account real work activity, more than to age-related natural characteristics.